Mergers and Acquisitions Accounting and the Diversification Discount - CUSTÓDIO, CLÁUDIA (Journal of Finance, 2014)
ABSTRACT q ‐based measures of the diversification discount are biased upward by mergers and acquisitions and its accounting implications. Under purchase accounting, acquired assets are reported at their transaction value, which typically exceeds the target's pre‐merger book value. Thus, measured q tends to be lower for the merged firm than for the portfolio of pre‐merger entities. Because conglomerates are more acquisitive than focused firms, their q tends to be lower. To mitigate this bias, I subtract goodwill from the book value of assets and a substantial part of the diversification discount is eliminated. Market‐to‐sales‐based measures do not have this bias.